Organizational Changes of the Daughter Basal Complex during the Parasite Replication of Toxoplasma gondii - Hu, Ke (Public Library of Science, 2008)

(untitled)
The apicomplexans are a large group of parasitic protozoa, many of which are important human and animal pathogens, including Plasmodium falciparum and Toxoplasma gondii. These parasites cause disease only when they replicate, and their replication is critically dependent on the proper assembly of the parasite cytoskeletons during cell division. In addition to their importance in pathogenesis, the apicomplexan parasite cytoskeletons are spectacular structures. Therefore, understanding the cytoskeletal biogenesis of these parasites is important not only for parasitology but also of general interest to broader cell biology. Previously, we found that the basal end of T. gondii contains a novel cytoskeletal assembly, the basal complex, a cytoskeletal compartment constructed in concert with the daughter cortical cytoskeleton during cell division. This study focuses on key events during the biogenesis of the basal complex using high resolution light microscopy, and reveals that daughter basal complexes are established around the duplicated centrioles independently of the structural integrity of the daughter cortical cytoskeleton, and that they are dynamic “caps” at the growing ends of the daughters. Compartmentation and polarization of the basal complex is first revealed at a late stage of cell division upon the recruitment of an EF-hand containing calcium binding protein, TgCentrin2. This correlates with the constriction of the basal complex, a process that can be artificially induced by increasing cellular calcium concentration. The basal complex is therefore likely to be a new kind of centrin-based contractile apparatus.